Development of a Green Chemistry-Based Practicum Module Integrated with Quranic Verses for Reaction Rate Material at SMA IT Darul Hikmah Pasaman Barat - Osriadi, Ukhti Amaliah; Mawarnis, Elvy Rahmi; Sari, Dwivelia Aftika (Edusainstika: Jurnal Pembelajaran MIPA, 2025)
This study aimed to develop a valid and practical green chemistry-based practicum module integrated with Qur'anic verses for teaching reaction rate concepts at SMA IT Darul Hikmah Pasaman Barat This study employed the Research and Development (R&D) method using the 4-D development model, which consists of the Define, Design, Develop, and Disseminate stages. However, this study was conducted only up to the Develop stage. The practicum module was tested on 17 female students from Class XI Akhwat. The research instruments used were validation sheets and practicality questionnaires. The results showed that the developed module received a highly valid category validation with A validity score of 91%. In addition, this module was declared very practical with a percentage of 90% based on educator responses and 86% based on student responses. The conclusion of this research is a practicum module based on green chemistry and integrated with Islamic values that is valid and practical so that it can be used as one of the teaching materials for chemistry learning.